2009
DOI: 10.1073/pnas.0903142106
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis reveals few genetic alterations in pediatric acute myeloid leukemia

Abstract: Pediatric de novo acute myeloid leukemia (AML) is an aggressive malignancy with current therapy resulting in cure rates of only 60%. To better understand the cause of the marked heterogeneity in therapeutic response and to identify new prognostic markers and therapeutic targets a comprehensive list of the genetic mutations that underlie the pathogenesis of AML is needed. To approach this goal, we examined diagnostic leukemic samples from a cohort of 111 children with de novo AML using single-nucleotide-polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 40 publications
(42 reference statements)
9
135
1
2
Order By: Relevance
“…79 In contrast to ALL, the analysis of CNAs in AML has yielded only a small number of CNAs in most genomes of adult and pediatric AML patients, and the spectrum of AML-associated CNAs seems to be mainly non-recurrent. [80][81][82] These findings collectively illustrate the enormous genetic heterogeneity of AML and suggest that the potential of the extensive catalogs of CNAs might be better exploited by future integrative analyses.…”
Section: Gepflink With Other 'Omics' Screeningsmentioning
confidence: 97%
“…79 In contrast to ALL, the analysis of CNAs in AML has yielded only a small number of CNAs in most genomes of adult and pediatric AML patients, and the spectrum of AML-associated CNAs seems to be mainly non-recurrent. [80][81][82] These findings collectively illustrate the enormous genetic heterogeneity of AML and suggest that the potential of the extensive catalogs of CNAs might be better exploited by future integrative analyses.…”
Section: Gepflink With Other 'Omics' Screeningsmentioning
confidence: 97%
“…Furthermore, a previously reported genome-wide study of pediatric AML revealed that, in contrast to our AML patients with IDH2 mutation, pediatric de novo AML was characterized by a very low burden of genomic alterations. 7 These clinical and cytogenetic data suggest that pediatric AML with t(8;21) and IDH2 mutation might be a specific subtype of AML with complex chromosomal abnormalities and poor prognosis. Thus, our result has important clinical and pathological implications regarding the role of IDH2 mutations in the development of AML.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Chez l'enfant, deux sous-groupes sont identifiés et représentent moins de 50 % des patients : (1) les LAM7 associées à la translocation t(1;22)(p13;q13) et à l'expression de la fusion OTT-MAL [3,4] décrite dans ces colonnes en 2009 [5] ; (2) celles qui se développent chez les patients porteurs d'une trisomie 21 constitutionnelle associée à des mutations du gène codant pour le facteur de transcription GATA-1 [6]. Les résul-tats d'une analyse génomique récente indiquent que les LAM7 pédiatriques présentent en moyenne 9,3 altérations structurelles par échantillon par comparaison avec 2,4 en moyenne pour les LAM en général et suggèrent l'existence d'autres anomalies chromosomiques [7]. Caractérisation génétique : le séquençage haut-débit du transcriptome permet l'identification de nouvelles anomalies chromosomiques (gauche : représentation en cercle des anomalies génomiques de structure) comme la fusion entre les gènes ETO2 et GLIS2 résultant d'une inversion du chromosome 16 (droite).…”
Section: Les Leucémies Aiguës à Mégacaryoblastesunclassified